School-to-Work Jump-Start Equity Kit - Education Development Center, Inc., Newton, MA. Women's Educational Equity Act Dissemination Center; Education Development Center, Inc., Newton, MA. Women's Educational Equity Act Dissemination Center ([S.l.] : Distributed by ERIC Clearinghouse, 1997)
This starter kit is a resource for state and local school-to-work (STW) directors, educators, parents, students, business and community, and economic development organizations serving all students through STW. The kit begins with four articles: "STW and Gender Equity: Opportunity for or Barrier to Economic Parity?" (Katherine Hanson, Joyce Malyn-Smith, Vivian Guilfoy); "Gender Equity: A Lens for Examining STW Issues" (Katherine Hanson); "Voluntary Industry Skill Standards: Integrated Standards and Equity" (Joyce Malyn-Smith, Vivian Guilfoy); and "Pregnant and Parenting Teens" (adapted from an article by Deborah Brake). Two sets of guidelines and seven activities for implementing equity in STW are divided into three categories: school-based learning, work-based learning, and connecting activities. The next section provides information on disaggregating the data. The next section consists of a Gender Equity and STW Fact Sheet and Women's Educational Equity Act Digests and articles: "The STW Opportunities Act" (Mary Wiberg); "Models for Serving All Students" (Jenny L. Erwin); "Mentoring in Educational Settings" (Olga M. Welch); "Learning from the Field" (Heidi Lynch); "Gender Equity in Vocational Education" (Debra J. Robbin); "Vocational Education in the School Reform Movement" (Sundra Flansburg); "Beyond Equal Access" (June Mark); and "Multicultural Education as Democratic Education" (Katherine Hanson). The next section lists 16 additional STW resources. A booklet, "School-to-Work: Equitable Outcomes," looks at gender in a multicultural context. It contains information on links between STW and gender equity and implementing gender-equitable STW, strategies, student equity-related competencies, equity checklist, and lists of 26 notes, 29 resources, and 12 organizations. (YLB)
Availability: WEEA Equity Resource Center, Education Development Center, 55 Chapel Street, Suite 285, Newton, MA 02158-1060; 800/225-3088; fax: 617/332-4318 (order no. 2766: $15 plus $3.50 shipping for first item, $.80 each additional item).
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Community.
Parents.
Practitioners.
May also be available online. Address as at 14/8/18
Keywords: Career Exploration; Check Lists; Cross Cultural Training; Disabilities; Early Parenthood; Education Work Relationship; Females; Guidelines; Learning Activities; Mentors; Nontraditional Occupations; Program Implementation; Secondary Education; Sex Fairness; Vocational Education; Womens Education; Guides, Non-Classroom.